Henri Lefebvre’s Concept Of Urban Space In The Context Of Preferences Of The Creative Classin A Modern City - Nadolny, Adam (Quaestiones Geographicae, 2015)
This article seeks to present how the manner of recording the spatial phenomena analysed by Henri Lefebvre in his numerous publications can serve as a basis for reflections on the suitability of his theories for the description of the creative class in a modern city. Because Lefebvre pursued a number of lines of thought in his philosophical ideas, we can state that there is a strong correlation between the city image he created and preferences of the creative class in a modern city. The article is also intended to make the reader realise that records of philosophical ideas can, in many instances, contribute to the improvement of the actual space in a city.